Subjective Well-Being of People with Different Profiles of Personality Openness - Iryna Kryazh; Natalia Levenets (Вісник Харківського національного університету імені В.Н. Каразіна. Серія: Психологія, 2023)
The article is devoted to the analysis of different approaches to the study of subjective well-being, with a focus on existential aspects, namely, on the role of existential fulfillment for the emotional and cognitive components of subjective well-being. Empirical research was carried out on a sample of student youth. The work uses the test of existential motivations by A. Lengle and P. Edhard, the subjective well-being scale of Perrudel-Badoux, Mendelsohn, and the life satisfaction scale of E. Diener. The nature of the relationship between four existential motivations and existential fulfillment in general with indicators of subjective well-being, life satisfaction and openness of the individual was established. Regression models describing the importance of fundamental motivations for subjective well-being and life satisfaction in the studied age group were built.